2020
DOI: 10.56964/pidspj20202101007
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile and Outcome of Admitted Pediatric Patients with Influenza

Abstract: Background: Influenza is one of the most common illnesses pediatricians face. Children are especially at risk for contracting influenza. Aside from fever, cough and colds, the disease may present differently in children. Complications due to influenza are varied and anti-virals may be useful if given early in the course of illness. Objectives: To determine the clinical profile of admitted pediatric patients with influenza based on rapid testing and determine its prevalence, outcome and complications. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…2 The demographic data presented in this study varies from what was presented by Reyes et al where majority of children with ILI were females with a mean age of 5-9 years old. Our findings of fever, cough, and colds were the most common presenting manifestation in patients with ILI in the pediatric population and were congruent with those of Reyes et al 15 Our study also showed that loose bowel movement, vomiting, and seizures were commonly manifested by the younger age group which suggest that influenza may be less distinct in younger children. 2,16 Non-specific symptoms such as chills, body malaise, sore throat, ear pain, abdominal pain, headache, and anorexia were prominent in the older age group and are also consistent with the clinical manifestations of influenza infection.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…2 The demographic data presented in this study varies from what was presented by Reyes et al where majority of children with ILI were females with a mean age of 5-9 years old. Our findings of fever, cough, and colds were the most common presenting manifestation in patients with ILI in the pediatric population and were congruent with those of Reyes et al 15 Our study also showed that loose bowel movement, vomiting, and seizures were commonly manifested by the younger age group which suggest that influenza may be less distinct in younger children. 2,16 Non-specific symptoms such as chills, body malaise, sore throat, ear pain, abdominal pain, headache, and anorexia were prominent in the older age group and are also consistent with the clinical manifestations of influenza infection.…”
Section: Discussionsupporting
confidence: 91%
“…Lack of vaccine coverage can be due to geographical factors, financial constraints, personal belief and lack of education on vaccination. 15 Our findings also indicate that there is no relation in symptoms of pediatric patients with ILI with vaccination history (p value = 0.970). One hundred percent of vaccinated and unvaccinated children experienced fever.…”
Section: Discussionmentioning
confidence: 47%
“…Rapid diagnosis of influenza viruses and early treatment with oseltamivir is crucial. 28 Therefore, influenza rapid testing may be done instead for Respiratory Panel in detecting Influenza virus. It is a highly sensitive and specific test and relatively cheaper than the Respiratory Panel.…”
Section: Discussionmentioning
confidence: 99%